Catalysts: Special Issue on Plasma-Catalysis for Environmental and Energy-Related Applications - Magureanu, Monica; Bradu, Corina (Catalysts, 2021)
Doping with other metals or metal oxides (alkali and alkaline earth metals—K and Mg, transition metals—Co and Mn, rare earth metals—La and Ce and their oxides) may prove beneficial, producing various effects such as enhancing resistance to carbon formation and even removing carbonaceous deposits, improving the Ni dispersion and inhibiting aggregation of Ni particles, strengthening the metal-support interaction, enhancing reactant adsorption, changing discharge characteristics as to increase the plasma area etc., ultimately leading to better plasma-catalyst synergy, higher CO2 and CH4 conversion and improved products distribution. The authors identified carbon monoxide, carbon dioxide, water and formic acid as main products in the gas phase of naphthalene decomposition, as well as several other complex gaseous and solid by-products, indicating incomplete oxidation of the target compound. Other organic by-products, such as methanol, acetic acid, methyl formate, methyl acetate, 1,2-ethanediol mono- and di- formate, were identified in the gas phase in both reactors as a result of the target compound decomposition, while acetone and nitromethane were only detected in the plasma-catalytic process. Detection of the carbonaceous intermediates provided more detailed information on acetaldehyde degradation in the plasma catalytic system by the interaction of adsorbed molecules with plasma-generated species and/or by-products of acetaldehyde decomposition in the gas phase. [...]the main degradation pathways could be identified.